2011
DOI: 10.1270/jsbbs.61.311
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of storage compounds and seed weight in rapeseed (Brassica napus L.) germplasms

Abstract: One thousand five hundred rapeseed accessions were collected from gene banks in several countries and surveyed for their seed traits such as oil content, protein content, fatty acid composition and seed weight. Seed chemicals were analyzed by near-infrared reflectance spectroscopy (NIRS). An extensive genetic variation existed among accessions for all seed traits examined. The oil content ranged from 24.7 to 56.9%, and the protein content ranged from 6.7 to 36.6%. A hundred seed weight ranged from 0.13 to 0.70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
(21 reference statements)
2
4
1
Order By: Relevance
“…3) oil and protein content were in highly significant negative correlation (r = -0.730). The results obtained in our experiment are in agreement with the report of Kennedy et al (2011). These authors also observed a highly significant negative correlation between oil and protein content (r = -0.848) in rapeseed, suggesting that oil content increases on account of protein content because of competition for the source of carbon.…”
Section: Variability and Correlation Between Oil And Protein Contentsupporting
confidence: 93%
“…3) oil and protein content were in highly significant negative correlation (r = -0.730). The results obtained in our experiment are in agreement with the report of Kennedy et al (2011). These authors also observed a highly significant negative correlation between oil and protein content (r = -0.848) in rapeseed, suggesting that oil content increases on account of protein content because of competition for the source of carbon.…”
Section: Variability and Correlation Between Oil And Protein Contentsupporting
confidence: 93%
“…In Arabidopsis , Hobbs et al ( 2004 ) reported that seed oil content was not significantly correlated with seed weight. Similar result was also observed in rapeseed that seed oil content was not significantly correlated with seed weight (Kennedy et al 2011 ). However, we still propose that higher silique and seed fresh and dry weight during seed embryo development stage in HOCL could be an important basis for obtaining high seed oil content.…”
Section: Discussionsupporting
confidence: 84%
“…The increase of the applied N dosage might increase the percentage of seed protein, as N is its major constituent [59]. Since the percentage of the oil content has an inverse relationship with the protein content [60][61][62], it can be a possible reason for the oil content decrease with the N increase.…”
Section: Time Of Sowing N Rates and Growing Seasonsmentioning
confidence: 99%